Investigation of thermal and viscoelastic properties of polymers relevant to hot melt extrusion - III: Polymethacrylates and polymethacrylic acid based polymers - Tapan Parikh; Simerdeep Singh Gupta; Anuprabha Meena; Abu T.M. Serajuddin (Journal of Excipients and Food Chemicals, 2016)
Polymers are a major part of final medicinal drug products prepared by hot melt extrusion (HME). Therefore it is necessary to understand their behavior when subjected to heat and mechanical stresses during the development of the HME processes. The aim of this work was to generate a database of the physicochemical properties for polymethacrylates and polymethacrylic acid based polymers relevant to HME. All six polymers tested were amorphous and had < 2% moisture. In differential scanning calorimetric (DSC) studies, the three homo block copolymers, Eudragit® E PO, Eudragit® RL PO and Eudragit® RS PO, had glass transition temperatures (Tg) of 57°C, 63°C and 64°C, respectively, and thermogravimetric analysis (TGA) showed weight loss due to thermal degradation at 250°C, 166°C and 170°C, respectively. Thermomechanical analysis was carried out to investigate the rheological properties of the polymers predicting that the melt extrusion ranges of Eudragit® E PO, Eudragit® RL PO and Eudragit® RS PO would be 127-150, 165-170 and 142-167°C, respectively. In contrast, the hetero block copolymers Eudragit® L 100, Eudragit® S 100 and Eudragit® L 100-55 had Tg values of 195, 173 and 111°C, respectively. Onsets of their degradation, as measured by TGA, were in the range of 173 to176°C. The predicted HME processing temperatures of Eudragit® L 100, Eudragit® S 100 and Eudragit® L 100-55 were greater than 200°C and therefore these polymers cannot be processed by themselves without the addition of plasticizers.